Table of Content - -, (Journal of Curriculum and Teaching Methodology, 2024)
Table of Content:1. The reality of implementing kindergarten (KG) female teachers for the standard of language development and early knowledge of reading and writing in teaching from the perspective of female educational supervisors in RiyadhHilalah Mohmmed Alarifi,  Prof. Dr. Helah Khalaf Aldoheman2. Teaching and human competencies necessary for the integrated education teaching staff from the perspective of directors and families in the primary education sector at the regional directorate of Inezgane Ait Melloul.ALI AIT ABBOU3. The level of inclusion of twenty-first-century skills in the mathematics textbook for the second grade of secondary school in the Kingdom of Saudi ArabiaIman Saed Almohammadi4. The Effect of Using Interactive E-activities on Motivation towards Learning and Academic Achievement of Tenth-Grade Female Students in the Information Technology and Computer courseMs. Manal Mohammed Al- Shamhani, Prof. Ahmed Bin Zaid Al Massad
Keywords: Journal of Curriculum and Teaching Methodology